Studi Literatur Perbedaan Ekspresi Messenger Ribonucleid Acid (mRNA) Reseptor Androgen Setelah Pemberian Testosteron antara Penis dan Kelenjar Prostat Tikus Wistar Jantan (Rattus Norvegicus) Pascakastrasi - Luh Ari Arini (JURNAL KESEHATAN REPRODUKSI, 2019)
Background: Aging process (andropause) in men will cause a decrease in testosterone hormones, in other that decrese of androgen receptor (testosteron and dhyhidrtestosterone) in target organ, can be seen from AR mRNA expression. Andropause finaly impact of male reproductive organ, so given testosterone hormone therapy is important to restore the condition. Giving testosterone hormone causes increase the expression of AR mRNA in the prostate gland and penis, but in these two organs there is a different increase.Objective: to know the difference of expression AR mRNA after administration of testosterone between prostate gland and penis.Method: This article used literature review from database of intisari sains medis.Results and Discussion: AR mRNA expression in the prostate gland is smaller than the penile tissue, due to the prostate gland in addition to the 5α reductase enzyme there are also many aromatase enzymes. In the normal prostate gland the amount of 5α reductase is small, so the addition of testosterone is converted to DHT but also in aromatization to estrogen. Therefore, fewer androgen receptors are found compared to the tissue of the penis, in addition expression of AR mRNA in the preputial penis is higher than the prostate gland.Conclusion: Penile tissue is more responsive to testosterone and improves the function and maintenance of tissue especially in old. Keywords: androgen receptor mRNA; testosterone; penis and prostate